2017
DOI: 10.3892/ol.2017.6935
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell‑expressed B7‑H3 regulates the differentiation of tumor‑associated macrophages in human colorectal carcinoma

Abstract: Abstract. Co-stimulatory molecule B7 homolog 3 protein (B7-H3) has been described as an important tumor antigen in various human tumors. The exact role of B7-H3 in tumor progression and its receptor are still ambiguous. The phenotype and the function of tumor-associated macrophages (TAMs) in human solid tumors are complicated and could contribute to the shaping of the tumor microenvironment. In the present study, B7-H3 expression and lymphocyte infiltration were investigated by immunohistochemistry in 117 colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…In addition, we found that there was a significant correlation between B7-H3 and CD68 expression. This result is consistent with our previous findings (24), and our group also found that B7-H3 regulates the differentiation of tumor-associated macrophages in human colorectal carcinoma (43). However, the correlation between B7-H3 and CD31 or α-SMA expression was much higher than that of B7-H3 and CD68 expression, suggesting that B7-H3 may play a vital role in the tumor microenvironment, including endothelial cells and fibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found that there was a significant correlation between B7-H3 and CD68 expression. This result is consistent with our previous findings (24), and our group also found that B7-H3 regulates the differentiation of tumor-associated macrophages in human colorectal carcinoma (43). However, the correlation between B7-H3 and CD31 or α-SMA expression was much higher than that of B7-H3 and CD68 expression, suggesting that B7-H3 may play a vital role in the tumor microenvironment, including endothelial cells and fibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…In colorectal carcinoma (CRC) tissues, expression of B7-H3 and infiltrating macrophage density were found to be positively associated, while both were negatively correlated with patients' survival rate. Since the presumed receptor of B7-H3 was found on activated monocytes and macrophages, these results further indicated the potential role of B7-H3 signal and macrophages in tumor progression [13]. High B7-H3 expression was found in human breast cancer tissues and may play an important role in tumor progression and invasiveness.…”
Section: Roles Of B7-h3 In Tumor Progression and Drug Resistancementioning
confidence: 58%
“…B7-H3 was found to be overexpressed among several kinds of human cancer cells and was correlated with disease deteriorations [13][14][15][16][17][18][19] (Table 2). B7-H3 was recognized as a co-stimulatory molecule for immune reactions such as T cell activation and IFN-γ production [20].…”
Section: Biological Function Of B7-h3mentioning
confidence: 99%
“…Hence, the function of B7-H3 in glioma may realized by the wide expression of B7-H3 in glioma cells and endothelial cells. Additionally, up-regulation of B7-H3 expression in macrophages has been reported in several cancers, 31,32 but the expression panel of B7-H3 in glioma associated macrophage is unknown. Here, for the first time, we showed that B7-H3 expression was significantly up-regulated in GBM infiltrating macrophages, indicating that B7-H3 may act as a potent adjunct to facilitating the immune evasion function of macrophages.…”
Section: Discussionmentioning
confidence: 99%